The barriers to flexibility : flexible rostering on the railways - Pendleton, Andrew [Verfasser] (My University, 1991)
"This paper reports a case study investigation of the implementation of flexible rostering in British Rail. It is found that this initiative did not secure readly identifiable improvements in flexibility or efficiency and indeed resulted in some new rigidities in work organisation. The national agreement introducing flexible rostering took a skeletal form, reflecting the priority in the public sector of reducing rather than adding to national level work regulation, and left potential conflicts with other agreements and practices to be resolved at the workplace. Workplace representatives were able to stamp their interests onto outcomes because local managers needed their expertise and consent to implement the scheme." (author's abstract) ((en)) Im Rahmen einer Fallstudie wird die Einführung des flexibeln Dienstplanes bei der britischen Eisenbahn untersucht. Im Ergebnis zeigt sich, dass die Anpassung der Arbeitszeiten an die Zugfahrpläne keine klar feststellbaren Verbesserungen in Hinblick auf Flexibilität oder Effizienz erbracht haben. Dies wird auf neue Starrheiten in der Arbeitsorganisation zurückgeführt, die sich aus arbeitsplatzspezifischen Praktiken und Vereinbarungen ergeben. (IAB)
Flexibilitätshindernisse. Flexible Dienstpläne bei der Eisenbahn
Keywords: G Gesellschaftlicher Kontext; S 2.2 Ordnungen & Ordnungsverfahren; G 1.2.3 Qualifikationsentwicklungen; G 1.2.4.2.2 Verkehr- und Nachrichtenübermittlung; S 6.4.2.1 Verkehrsberufe (inkl. Nachrichtenverkehr); G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 2.3.1 Arbeitsteilung & -organisation; G 1.2.2.1 Lohn- & Tarifsysteme; Arbeit; Flexibilität; Schienenverkehr; Schienenfahrzeugführer; Arbeitszeitflexibilisierung; Lohnfindung; Berufsproblem